A novel complement C3 like gene (Lv-C3L) from Litopenaeus vannamei with bacteriolytic and hemolytic activities and its role in antiviral immune response. Issue 91 (August 2019) - Liu, Yichen; Song, Qiaozhen; Li, Danlei; Zou, Ruifeng; Zhang, Yichen; Hao, Shaoyan; Geng, Xuyun; Sun, Jinsheng
Abstract: As a core component of the complement system, complement component 3 (C3) plays a central role in the opsonization of pathogens, immune defense and immune regulation in the mammalian for its activation is required to trigger classical as well as alternative complement pathways. However, the molecular mechanism underlying C3 activation in invertebrates remains unknown. Several C3 genes have been characterized in invertebrates but very few in crustacean. To understand the molecular characterization and immunological functions of shrimp C3, we characterized a novel complement C3 like gene (designated Lv-C3L ) with full-length cDNA sequence identified from pacific white shrimp Litopenaeus vannamei in the present study. The full length cDNA of Lv-C3L sequence was 4769 bp (GenBank accession number: MH638255) containing a 4077 bp open reading frame (ORF), which encodes 1358 amino acids contained a putative signal peptide of 17 amino acids. Six model motifs of C3 were found in Lv-C3L including typical A2M domain, a highly conserved thioester region (GCGEQ) and proteolytic cleavage site of ANATO. In addition to typical conservative domains, Lv-C3L also contains a particular GLN-rich region which might be involved in the protein interaction and transcriptional activation. The transcripts of Lv-C3L were mainly detected in hemocytes and gill which might be involved in defense response. At 36 h post V.parahaemolyticus and B.thuringensis infection, the expression level of Lv-C3L gene in hemocytes were significantly upregulated. At 48 h and 72 h post WSSV infection, the expression level of Lv-C3L gene in hemocytes and gill were significantly upregulated. These results indicated that Lv-C3L gene play a pivotal role in innate immune responses to the WSSV and G + /G − bacterial infection. The obvious immune function of Lv-C3L was described as an effective membrane rupture in bacteriolytic and hemolytic activities on V.parahaemolyticus, V.anguillarum and rabbit erythrocytes. Combining with WSSV copy number, WSSV- VP28 gene expression profile and shrimp cumulative mortality analysis, RNAi knockdown of Lv-C3L gene could obviously promote the in vivo propagation of WSSV in shrimp. This is the first report in crustaceans that Lv-C3L, as a key complement like components, is involved in shrimp antiviral immune response. It is speculated that complicated complement response cascade may exist in shrimp. These results collectively indicated that the complement pathway in shrimp might play an important protective role against pathogenic infection and activation of complement pathway including C3 could restrict the propagation of WSSV. Highlights: A novel complement C3 like gene ( Lv-C3L ) was cloned from hemocytes of L. vannamei in this manuscript. The expression level of Lv-C3L gene in hemocytes and gill were significantly upregulated after bacterial and WSSV infection. The obvious immune function of Lv-C3L was described as an effective membrane rupture in bacteriolytic and hemolytic activities. RNAi knockdown of Lv-C3L gene could obviously promote the in vivo propagation of WSSV in shrimp.